The Role of The Greek Borrowings In Albanian Lexis - Sofia DELIGEORGI (Association of Social and Educational Innovation, 2015)
The purpose of this study is to distinguish the Greek borrowings in Albanian language and to define their role in the layers of the Albanian lexis. Even though Albanian is an Indo-European language, this fact does not mean that its entire lexical fund stems from its mother language Illyrian. The contacts and the relations with the other nations have brought even influences on the language. Borrowing the words in Albanian has come as a necessity to nominate an object or a concept under some certain historical and linguistic circumstances. The types of the borrowings and the historical periods which mark the access of these words in Albanian lexis are clearly specified in the study. Every historical concept is provided with examples, which are encountered in the dictionaries but even in the dialects of different regions, or with old words which are used in daily life.